Food-feed crops research: A synthesis - Pattanaik, A.K.; Sharma, K.; Samireddypalle, A.; Blümmel, Michael (2010)
The present paper synthesizes the salient findings of the 16 papers included in this special issue on food-feed crops. While summarizing the approaches and outcomes of the research papers, the synthesis also discusses related issues, which are of importance in delineating the future research agenda on this important topic. Cereal crop residues (CCRs) constitute the single most important fodder resource providing more than 40% of the available dry matter for feeding of ruminants. However, the inherent low nutritive value typical to most CCRs is a handicap in the effective utilization of this vast feed resource. The synthesis paper besides providing an update on the progress in food-feed crop research, suggests future approaches to exploit the variability in fodder quality traits for improving livestock productivity. It also highlights the need for the plant and animal scientists to work in tandem to achieve this goal. It also stresses the need for greater integration, focus, coordination of efforts to improve the utilization of food– feed crops.